2016
DOI: 10.1038/ejhg.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

A non-coding variant in the 5ʹ UTR of DLG3 attenuates protein translation to cause non-syndromic intellectual disability

Abstract: Intellectual disability (ID) is a clinically complex and heterogeneous disorder, which has variable severity and may be associated with additional dysmorphic, metabolic, neuromuscular or psychiatric features. Although many coding variants have been implicated in ID, identification of pathogenic non-coding regulatory variants has only been achieved in a few cases to date. We identified a duplication of a guanine on chromosome X, NC_000023.10:g.69665044dupG 7 nucleotides upstream of the translational start site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…The main clinical features of the male proband of the family reported here (moderate ID and absence of other major health problems) are in accordance with those of previously published patients with DLG3 mutations (Table ) (Isrie et al, ; Kumar et al, ; Philips et al, ; Tarpey et al, ; Tzschach et al, ; Zanni et al, ). Also some of the dysmorphic features have been reported before: a triangular face is reminiscent of the patient reported by Isrie et al () and a narrow thorax was present in family D172 of Philips et al () (Isrie et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The main clinical features of the male proband of the family reported here (moderate ID and absence of other major health problems) are in accordance with those of previously published patients with DLG3 mutations (Table ) (Isrie et al, ; Kumar et al, ; Philips et al, ; Tarpey et al, ; Tzschach et al, ; Zanni et al, ). Also some of the dysmorphic features have been reported before: a triangular face is reminiscent of the patient reported by Isrie et al () and a narrow thorax was present in family D172 of Philips et al () (Isrie et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Figure S2). Cognitive impairment of the affected males ranged from mild to severe ID and some patients had additional symptoms including seizures, abnormal behavior, and facial dysmorphisms (Table ) (Isrie et al, ; Kumar et al, ; Philips et al, ; Tarpey et al, ; Tzschach et al, ; Zanni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Blood products can contain a mixed population of EVs, including exosomes and microvesicles, which are heterogeneous submicron-sized vesicles surrounded by a phospholipid bilayer containing proteins, lipid, and a variety of RNA molecules [26,27,28,29,30]. The presence of EVs in stored RCC products, which accumulate during storage, has been identified as a significant indicator of storage lesion [4,5,31,32]. Based on the current knowledge, it has been suggested that EVs in stored blood are associated with a number of adverse outcomes such as neutrophil activation and promoting an inflammatory response in the recipients of older blood [33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The quality assurance of the blood components is vital during processing and storage for the patient safety [3]. Although several accomplishments have been made to maintain the integrity and function of blood cells and to improve the quality of stored blood components for better transfusion outcomes [4,5,6,7,8], a number of studies have revealed that transfusion of red blood cell (RBC) products is still associated with increased risk of adverse clinical events [9,10,11,12,13,14,15]. Many recent studies have focused on effects of storage duration on the quality of blood products and their clinical consequences [10,11,13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Seven of the synaptic genes (DLG3, MECP2, KAL1, SYN1, ARHGAP4, NLGN4X and AR) are listed by Genecards as schizophrenia-related (27)(28)(29)(30)(31)(32)(33). DLG3 is critical for synaptogenesis and required for learning most likely through its role in synaptic plasticity (34). Piton et al found that MECP2, the main Rett syndrome gene, showed an accumulation of non-synonymous rare variants in schizophrenics (26).…”
Section: Synaptic Genesmentioning
confidence: 99%